In situ oxidation transformation of trimetallic selenide to amorphous FeCo-oxyhydroxide by self-sacrificing MoSe₂ for efficient water oxidation - Tang, Yu-Jia (2022)
Transition metal chalcogenides have emerged as unique electrocatalysts for the oxygen evolution reaction (OER) during which they usually undergo an oxidation transformation into active oxides/(oxy)hydroxides. However, the transformation is so rapid that a high exposure of as-transformed (oxy)hydroxides cannot be achieved, thereby hindering the OER efficiency of the electrocatalyst. Herein, we report a simple self-sacrificing strategy to increase this exposure. A trimetallic selenide heterostructure (FeCoMo-Se) consisting of FeSe₂, CoSe₂ and MoSe₂ is first one-step synthesized on a carbon cloth substrate. The heterostructure possesses a thin nanosheet morphology due to the support of MoSe₂ nanosheets as a structural template. Under OER conditions, FeSe₂ and CoSe₂ are then in situ converted to FeCo-oxyhydroxide while retaining the nanosheet morphology of the heterostructure. Interestingly, MoSe₂ is self-sacrificially dissolved and hence leaves considerable space to increase the exposure of FeCo-oxyhydroxide to the electrolyte. Such an advantageous nanostructure endows the FeCoMo-Se-transformed electrocatalyst with excellent OER performance in an alkaline medium, which is much higher than the non-MoSe₂-containing selenide FeCo-Se. Density functional calculations demonstrate the favorable intermediate bindings in FeCo-oxyhydroxide. This novel self-sacrificing strategy opens up new avenues in the development of high-performance OER electrocatalysts with respect to their in situ oxidation transformation.